What's the Beef in South Korea Protests?: The Technical, Psychometric, and Sociocultural Dimensions of News Coverage of Risk. Issue 2 (2nd July 2016) - Rodriguez, Lulu; Lee, Suman
ABSTRACT: Millions of South Koreans took to the streets for more than 2 months in 2008 ostensibly in protest over their government's handling of beef imports from the United States. This study examines the technical, psychometric, and sociocultural dimensions of these public protests by conducting a content analysis of the coverage of the English language daily newspaper The Korea Herald . The results suggest that the scarcity of technical risk assessment information and the preponderance of normative or outrage factors in the newspaper's coverage (lack of trust in government, perceptions of inequity, and unequal benefits accruing to both nations) may have fueled public anxiety and anger. The findings also point to social, cultural, and historical factors that may explain why allowing U.S. beef into the Korean market elicited strong public reactions.